2017
DOI: 10.3354/esr00728
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sea turtle exposures to Deepwater Horizon oil

Abstract: The Deepwater Horizon (DWH) oil spill was unprecedented in extent and duration, and affected marine natural resources, including sea turtles, throughout the northern Gulf of Mexico. Consequently, US federal and state Trustees documented and quantified oil exposure and resulting injuries to sea turtles under the DWH Natural Resource Damage Assessment. At-sea rescue operations focused on surface-pelagic juvenile sea turtles, which were especially at risk to oil exposure within oceanic convergence zones, and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This result is consistent with rapid transit of waters across the northern GoM. Under this simplification, we envisioned that each turtle at a 'fixed' location would be exposed to oil when the model of Wallace et al (2017) estimated the turtle's location had non-zero probability of heavy oiling. The results of this method provided the areal extent to which turtle densities were ap plied.…”
Section: Total Exposuresupporting
confidence: 63%
See 3 more Smart Citations
“…This result is consistent with rapid transit of waters across the northern GoM. Under this simplification, we envisioned that each turtle at a 'fixed' location would be exposed to oil when the model of Wallace et al (2017) estimated the turtle's location had non-zero probability of heavy oiling. The results of this method provided the areal extent to which turtle densities were ap plied.…”
Section: Total Exposuresupporting
confidence: 63%
“…Because their model utilized satellite-based daily estimates of surface oiling, the model indirectly incorporated currents, convergence zones, and general circulation of waters in the northern Gulf during the spill period. Wallace et al (2017) found that the majority of locations, and hence the majority of fixed turtle locations within the footprint, had a positive average probability of heavy oiling during the study (Fig. 4).…”
Section: Total Exposurementioning
confidence: 90%
See 2 more Smart Citations
“…These areas were heavily contaminated by oil during and after the spill (Fig. 1), and both direct observation (Wallace et al 2017) and post-spill modeling of the oil trajectory (Putman et al 2015) indicated that many Lk were exposed.…”
mentioning
confidence: 99%